2015
DOI: 10.1016/j.mex.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of isometric dorsiflexion protocol for assessment of tibialis anterior muscle strength

Abstract: Graphical abstractA comparison of the existing isometric dorsiflexion protocol (Setting 1) and the proposed improvement of the protocol which includes the fixation of the toes in addition to fixing the ankle and foot (Setting 2) are shown. The triceps surae muscle group comprises of the lateral gastrocnemius (LG), medial gastrocnemius (MG) and soleus (SOL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The IMUs were placed on the Medial Gastrocnemius muscle (MG) and Tibialis Anterior (TA) muscles of the left and right legs as shown in Figure 1 and the positioning was based on the SENIAM recommendation [45]. The sensor placed in the TA muscle was used to compute the gait intervals, which was considered the best location to study gait events [46].…”
Section: Methodsmentioning
confidence: 99%
“…The IMUs were placed on the Medial Gastrocnemius muscle (MG) and Tibialis Anterior (TA) muscles of the left and right legs as shown in Figure 1 and the positioning was based on the SENIAM recommendation [45]. The sensor placed in the TA muscle was used to compute the gait intervals, which was considered the best location to study gait events [46].…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus was developed in consultation with clinicians, and was developed to be MR‐safe, low cost, sturdy and easily constructed. The set‐up followed recommendations for accurate estimation of maximum voluntary contraction of the targeted tibialis anterior muscle through use of a strap placed tightly over the toes (Siddiqi et al, 2015). By introducing individualized resistance to a small amplitude movement, the task appears accessible to children with a wide range of abilities and provides a method to normalize subjective task difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…This small, active movement range is available to most children with UCP (Nordmark et al, 2009). The participant's foot was secured to a hinged pedal using two padded Velcro straps, with one strap over the toes following recommendations for assessment of isolated tibialis anterior activation (Siddiqi et al, 2015). The heel was placed on a constructed ledge just above the hinge point.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedures used in this study have been reported in our earlier studies. 31,26,56 Experimental protocol. This study protocol was approved by the 'RMIT University Human Research Ethics Committee' (SEHAPP 15751 (40/13)) and was carried out in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%